HLA‐DQ allele‐restricted activation of nitroso sulfamethoxazole‐specific CD4‐positive T lymphocytes from patients with cystic fibrosis. Issue 8 (August 2015) - Ogese, M. O.; Saide, K.; Faulkner, L.; Whitaker, P.; Peckham, D.; Alfirevic, A.; Baker, D. M.; Sette, A.; Pirmohamed, M.; Park, B. K.; Naisbitt, D. J.
Summary Background For certain HLA allele‐associated drug hypersensitivity reactions, the parent drug has been shown to associate directly with the risk allele. In other forms of hypersensitivity, HLA risk alleles have not been identified and T cells are activated in an allele unrestricted manner. Chemically reactive drug metabolites bind to multiple proteins; thus, it is assumed that the derived peptide antigens interact with a number of HLA molecules to activate T cells; however, HLA restriction of the drug metabolite‐specific T‐cell response has not been studied. Objective To utilize T cells from sulfamethoxazole (SMX) hypersensitive patients with cystic fibrosis to examine the HLA molecules that interact with nitroso SMX (SMX‐NO)‐derived antigens. Methods T‐cell clones were generated from 4 hypersensitive patients. Drug‐specific proliferative responses and cytokine secretion were measured. Anti‐human class I and class II antibodies were used to analyse HLA restriction. Antigen‐presenting cells expressing different HLA molecules were used to determine the alleles involved in the presentation of SMX‐NO‐derived antigens to T cells. Results A total of 976 clones were tested for SMX‐NO reactivity. Thirty‐nine CD4+ clones were activated with SMX‐NO and found to proliferate and secrete cytokines. The SMX‐NO‐specific response was blocked with an antibody against HLA‐DQ. SMX‐NO‐specific responses were detected with antigen‐presenting cells expressing HLA‐DQB1*05:01 (patient 1) and HLA‐DQB1*02:01 (patient 2), but not other HLA‐DQB1 alleles. Conclusion and Clinical Relevance HLA‐DQ plays an important role in the activation of SMX‐NO‐specific CD4+ T cells. Detection of HLA‐DQ allele‐restricted responses suggests that T cells are activated by a limited repertoire of SMX‐NO‐modified peptides.